Brief Report: Cross-Modal Capture: Preliminary Evidence of Inefficient Filtering in Children with Autism Spectrum Disorder. - Keehn, Brandon; Westerfield, Marissa; Townsend, Jeanne (Journal of Autism & Developmental Disorders, 2019)
This study investigates how task-irrelevant auditory information is processed in children with autism spectrum disorder (ASD). Eighteen children with ASD and 19 age- and IQ-matched typically developing (TD) children were presented with semantically-congruent and incongruent picture-sound pairs, and in separate tasks were instructed to attend to only visual or both audio-visual sensory channels. Preliminary results showed that when required to attend to both modalities, both groups were equally slowed for semantically-incongruent compared to congruent pairs. However, when asked to attend to only visual information, children with ASD were disproportionally slowed by incongruent auditory information, suggesting that they may have more difficulty filtering task-irrelevant cross-modal information. Correlational analyses showed that this inefficient cross-modal attentional filtering was related to greater sociocommunicative impairment.